KONSEP BULUIH DALAM PERTUNJUKAN LUAMBEK PADA MASYARAKAT SICINCIN DI MINANGKABAU - Yusfil, Yusfil; Saaduddin, Saduddin; Gusmail, Sabri (Studi Budaya Nusantara, 2020)
The study of the concept of Buluih in Luambek performances among the Sicincin community in Minangkabau aims to describe the function and aesthetic value of the concept of buluih in Luambek performances among the Sicincin community. The concept of buluih is one of the attractions that has a function and aesthetic value, making Luambek performances a cultural heritage that remains preserved in the community. The presence of Buluih in the Luambek dramaturgy is reflected through the movements produced and integrated with the concept of life in the Sicincin community, making the performance well-received by the community. The analysis employed combines The Liang Gie's aesthetic concept with Richard Kraus's functional theory. This study utilises a qualitative research method with an aesthetic approach, employing observation, interviews, and literature review as data collection techniques. The research findings indicate that Luambek possesses aesthetic value due to its sensory-evaluable form and its life value, which positions the concept of buluih as the primary benchmark for upholding the reputation of the community (tribe) during major traditional ceremonies within that community (tribe).